Surgical Management of Non-Reducible Congenital Umbilical Hernia in a Piglet - Kaushik, Rashmi; Sharma, AK; Reetu; Kumar, Bidyabhushan; Kumar, Vinod; Oraon, Sunil (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
An umbilical hernia is one of the most common developmental defects in swine (Edwards and Mulley, 1999). These hernias result in economic loss because they can affect pig performance and market value (Morrow et al., 2006; Straw et al., 2008; Mattsson, 2011). Hernia is classified as a reducible or irreducible hernia